Current Role and Future Perspectives of Radioiodinated MIBG in the Evaluation of Dementia with Lewy Bodies - Treglia, Giorgio; Ceriani, Luca; Giovanella, Luca (Current Radiopharmaceuticals, 2014)
Dementia with Lewy bodies (DLB) is the second most common cause of degenerative dementia after Alzheimer’s disease (AD). To improve the diagnosis of DLB, the latest diagnostic criteria incorporate findings from neuroimaging studies including sympathetic innervation imaging with iodine-123-metaiodobenzylguanidine (MIBG). According to these criteria a decreased MIBG myocardial uptake is an important finding supporting a clinical diagnosis of DLB. In this review the state of art and future perspectives of sympathetic innervation imaging by using MIBG in the diagnosis of DLB are discussed.
Keywords: innervation imaging